Looking into Students’ Cognitive Processes in an Online Collaborative Learning Environment - Díaz-Chang, Tamara; Arredondo, Elizabeth-H (International Journal of Emerging Technologies in Learning (iJET), 2024)
The primary aim of this study was to examine how students’ cognitive interactions in an online collaborative environment influence the formation and recognition processes of unconscious cognitive mechanisms appearing in the learning of mathematical concepts at the university level. The data analyzed was collected from a population of undergraduate students. The implemented methodology was supported by a qualitative approach. The study occurred in two phases: in the first phase, students answered three questionnaires, and in the second phase, stimulated recall interviews involving the verbalization of the cognitive processes were conducted retrospectively through the online collaborative environment provided by Zoom. The selection of pairs of students participating in these interviews was made after analyzing their responses, considering their richness in terms of differences and variations. Through the study, rich insights were gained into the cognitive processes examined. The analysis showed metacognitive processes through which students’ unconscious misconceptions were examined through self-reflection on previously acquired inadequate schemas. Cognitive and metacognitive interactions during the interviews progressively led to an adequate understanding of mathematical concepts. The findings confirm the results of a similar study that states stimulated recall data gathered in collaborative environments could be useful in revealing relatively higher-level cognitive and metacognitive processes.